2021
DOI: 10.3389/fimmu.2021.719009
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Promotes a Mixed Inflammatory-Fibrotic Macrophages Phenotype in Active Sarcoidosis

Abstract: BackgroundMacrophages are pivotal cells in sarcoidosis. Monocytes-derived (MD) macrophages have recently been demonstrated to play a major role especially in pulmonary sarcoidosis. From inflammatory tissues to granulomas, they may be exposed to low oxygen tension environments. As hypoxia impact on sarcoidosis immune cells has never been addressed, we designed the present study to investigate MD-macrophages from sarcoidosis patients in this context. We hypothesized that hypoxia may induce functional changes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 71 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…PAI-1, also called "serpin family E member 1 (SERPINE1)," a member of the serine proteinase inhibitor (serpin) superfamily, has been shown to promote fibrosis in multiple organ systems and function as a component of innate antiviral immunity. Florence Jeny et al identified that hypoxia increased the profibrotic response with PAI-1 secretion associated with human lung fibroblast migration inhibition in monocyte-derived (MD) macrophages among highly active sarcoidosis patients (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1, also called "serpin family E member 1 (SERPINE1)," a member of the serine proteinase inhibitor (serpin) superfamily, has been shown to promote fibrosis in multiple organ systems and function as a component of innate antiviral immunity. Florence Jeny et al identified that hypoxia increased the profibrotic response with PAI-1 secretion associated with human lung fibroblast migration inhibition in monocyte-derived (MD) macrophages among highly active sarcoidosis patients (56).…”
Section: Discussionmentioning
confidence: 99%
“…Florence Jeny et al. identified that hypoxia increased the profibrotic response with PAI-1 secretion associated with human lung fibroblast migration inhibition in monocyte-derived (MD) macrophages among highly active sarcoidosis patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia, as recent studies suggest, may promote a mixed inflammatory/fibrosing response of macrophages involved in the development and persistence of granulomas in active sarcoidosis and fibrosis surrounding granulomas by reducing their antigen presentation capacities that results in a deficient T cell response [29 ▪ ]. Hypoxia could have a significant impact in patients with highly active disease and the HIF pathway and PAI-1 can represent new therapeutic targets of active sarcoidosis.…”
Section: From Granuloma To Progressive Fibrosismentioning
confidence: 99%
“…In the context of respiratory viral diseases, such as influenza and COVID-19 patients, researchers have found that patients with these lower respiratory viral infections often develop hypoxemia, primarily because crosstalk between lung inflammation and a hypoxic microenvironment may impair pulmonary ventilation [ 35 ]. Hypoxia may also promote tissue inflammation–fibrosis [ 36 ]. In active nodular diseases, hypoxia promotes fibrosis through a pro-fibrotic cytokine response.…”
Section: The Implications Of Hypoxiamentioning
confidence: 99%